Comentario analítico a la propuesta de la reforma educativa en Colombia (2012)
The present test, it arises from the academic worry for understanding critically the porqué of the offer of reform to the system of Top Public Education wants to be implemented in Colombia, for it, it contributes a theoretical tool that helps to analyze and debate the consequences of these processes of reform, especially the intervention of the capital deprived in the Top public Education, and in addition allow, to know and to spread the processes of debate opened, in relation with them, by the sectors of the company compromised with the deepening of the democracy and the social equality.